Enhancement of ferroptosis by boric acid and its potential use as chemosensitizer in anticancer chemotherapy. (5th December 2022) - Corti, Alessandro; Dominici, Silvia; Piaggi, Simona; Pompella, Alfonso
Abstract: Ferroptosis is a form of regulated cell death (RCD) characterized by intracellular iron ion accumulation and reactive oxygen species (ROS)‐induced lipid peroxidation. Ferroptosis in cancer and ferroptosis‐related anticancer drugs have recently gained interest in the field of cancer treatment. Boron is an essential trace element playing an important role in several biological processes. Recent studies have described contrasting effects of boric acid (BA) in cancer cells, ranging from protective/mitogenic to damaging/antiproliferative. Interestingly, boron has been shown to interfere with critical factors involved in ferroptosis—intracellular glutathione and lipid peroxidation in the first place. Thus, the present study was aimed to verify the ability of boron to modulate the ferroptotic process in HepG2 cells, a model of hepatocellular carcinoma. Our results indicate that—when used at high, pharmacological concentrations—BA can increase intracellular ROS, glutathione, and TBARS levels, and enhance ferroptosis induced by RSL3 and erastin. Also, high BA concentrations can directly induce ferroptosis, and such BA‐induced ferroptosis can add to the cytotoxic effects of anticancer drugs sorafenib, doxorubicin and cisplatin. These observations suggest that BA could be exploited as a chemo‐sensitizer agent in order to overcome cancer drug resistance in selected conditions. However, the possibility of reaching suitably high concentrations of BA in the tumor microenvironment will need to be further investigated.